Commitment of Educators in Islamic Boarding Schools (Study at Islamic Boarding Schools in Cilacap Regency) - Fathul Aminudin Aziz (Ijtimā`iyya: Journal of Muslim Society Research, 2019)
Islamic boarding school institution is one of the oldest institutions in Indonesia, but its development is slower when it’s compared to other institutions. Researcher felt the need to analyze about the influence of organizational development, leadership and communication toward employee motivation, commitment and the implications for boarding school teachers in Cilacap. To test the model and hypotheses, researcher used analysis of Structural Equation Model (SEM). Furthermore, to estimate the model, the author used the program Analysis of Moment Structures (AMOS). Based on the research of 371 respondents from Islamic boarding school teachers in Cilacap regency, it could be concluded that (1) organizational development, leadership and organizational communication give positive and significant impact on work motivation, either partially or simultaneously, (2) organizational development, leadership, organizational communication and work motivation give positive and significant impact on the commitment of Islamic boarding school teachers, either partially or simultaneously. Results of this study recommend that the commitment of Islamic boarding school teachers can be improved by motivating teachers in internal dimensions, especially those associated with the indicator in the form of an appreciation of science / diploma.